A review of international labeling policies of genetically modified food to evaluate India’s proposed rule - Gruère, Guillaume P. P.; Rao, S. R. (2007)
This paper provides a comprehensive review of existing international labeling policies of genetically modified (GM) food and associated relevant international agreements in order to evaluate India’s proposed mandatory labeling rule. Existing evidence from developed countries shows that mandatory labeling regulations have resulted in no additional consumer choice or information. Among the few developing countries with labeling policies, most have not effectively implemented their regulations. We show that India’s proposed labeling rules for GM food would be among the most stringent globally and could potentially result in low consumer benefits at a high cost both domestically and internationally. India’s proposed regulation also lacks a number of elements to be implemented. However, these conclusions are based on experiences from other countries and limited available information from India. More studies are needed to evaluate the potential economic effects of GM food labeling in India.